2020
DOI: 10.1002/adma.202004452
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging mRNA Sequences and Nanoparticles to Deliver SARS‐CoV‐2 Antigens In Vivo

Abstract: SARS-CoV-2 vaccines based on inactivated live virus, recombinant viral vector, mRNA, DNA, and recombinant protein are currently in clinical trials. [6] Among these agents, an mRNA-based vaccine candidate quickly entered the clinical trial, because of the fast process for developing and manufacturing mRNA. [7] In order to express an antigen effectively, an mRNA requires several essential components, including 5′ cap, 5′ untranslated region (5′ UTR), antigen-encoding sequence, 3′ untranslated region (3′ UTR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 49 publications
(69 reference statements)
0
91
0
Order By: Relevance
“…Advancement in nucleic acid delivery has increased the potential for nucleic acid vaccines to enhance immunogenicity [ 263 , 274 ]. Diverse methods have been applied for successful penetration of the lipid membrane including physical methods [ 275 , 276 ], cationic peptide delivery [ 277 ], lipid, and polymer-based delivery [ 278 , 279 ]. Lipid nanoparticles (LNPs) have become one of the most favorable tools for mRNA delivery consisting of four main components: An ionizable cationic lipid, lipid-linked polyethylene glycol (PEG), cholesterol, and naturally occurring phospholipids.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…Advancement in nucleic acid delivery has increased the potential for nucleic acid vaccines to enhance immunogenicity [ 263 , 274 ]. Diverse methods have been applied for successful penetration of the lipid membrane including physical methods [ 275 , 276 ], cationic peptide delivery [ 277 ], lipid, and polymer-based delivery [ 278 , 279 ]. Lipid nanoparticles (LNPs) have become one of the most favorable tools for mRNA delivery consisting of four main components: An ionizable cationic lipid, lipid-linked polyethylene glycol (PEG), cholesterol, and naturally occurring phospholipids.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…[ 74 ] In a recent work, they utilized a combination of rationally engineered NASAR mRNA with TT3 NPs to deliver mRNA vaccine for SARS‐CoV‐2. [ 75 ] NASAR mRNAs were produced through a rigorous process of global gene expression bioinformatics scanning including analysis of copies produced/mRNA molecule, amino acids produced/mRNA molecule, along with many other factors such as endogenous/de novo UTR selection, nucleotide length/composition optimization, removal of miRNA target sites and integration of beneficial RNA motifs. The TT3‐formulated NASAR mRNA vaccine for SARS‐CoV‐2 was shown to induce 300‐fold more anti‐S1 antibodies than MC3 (an FDA‐approved lipid‐based delivery vehicle), and additionally intramuscular injection induced fivefold more antigen‐specific antibodies than subcutaneous injection.…”
Section: Nanoparticles Are An Advantageous Methods For Delivering Nucleic Acid Vaccinesmentioning
confidence: 99%
“…Trepotec et al designed a 14-nt-long 5′ UTR sequence that produces a comparable level of expression compared to human alpha-globin 5′ UTR [ 33 ]. Zeng et al designed de novo 5′ UTR sequences based on the length and guanine-cytosine content as well as predicted resistance of resulting mRNA to miRNA for the development of mRNA vaccines [ 34 ]. Recent advances in big data and machine learning have enabled predicting and designing regulatory sequences in silico [ 35 ].…”
Section: Mrna Vaccinesmentioning
confidence: 99%
“…The latter was surprisingly selective towards the spleen (about 85%) and able to transfect B cells, highlighting that small structural variations can lead to tissue selectivity [ 206 ]. In another study, Li et al reported TT3 as a potent delivery agent for various mRNA molecules encoding Factor IX [ 207 ], CRISPR/Cas9 [ 208 ], and more recently viral antigens against SARS-CoV-2 [ 34 ]. The structures of the lipidoids are enlisted in Fig.…”
Section: Materials For Mrna Deliverymentioning
confidence: 99%